Impact of prognostic nutritional index on survival in recurrent glioblastoma [Impacto de Prognostic Nutritional Index en la supervivencia de los glioblastomas recurrentes] - (:unkn) unknown (Neurocirugia, 2022)
Background: Primary brain tumors are relatively rare malignancy, with high-grade gliomas (glioblastoma multiforme and anaplastic gliomas) are the most common types. We aimed to evaluate the prognostic value of Prognostic Nutritional Index (PNI), which is calculated by lymphocyte count and albumin, in recurrent glioblastoma patients treated with systemic treatment. Methods: Data of 64 patients with recurrent glioblastoma who received systemic treatment and followed in our clinic between 2012 and 2018 was retrospectively collected and analyzed. PNI was calculated as: [(10 × serum albumin (g/dL)) + (0.005 × total lymphocyte count)]. Patients were categorized according to the median PNI value. We investigated the prognostic role of PNI groups, and survival outcomes. Results: Median value of PNI was 45.7, and median follow-up duration was 9 months (1–68 months). Median overall survival (OS) was 7.9 months (95%CI: 5.5–10.4). Median OS was significantly longer in patients with PNI > 45.7 compared to patients with PNI ≤ 45.7 (13.9 months (95%CI: 10.5–17.4), and 4.6 months (95%CI: 2.5–6.8), p < 0.001, respectively). In multivariate analysis, PNI was found to be an independent prognostic factor for OS [HR:0.41 (95%CI:0.22–0.74), p = 0.03)]. Conclusion: In our study, the PNI was found to be an independent prognostic biomarker in patients with recurrent glioblastoma, but further prospective trials are necessary to validate its prognostic role. © 2020 Sociedad Española de Neurocirugía
Keywords: Glioblastoma; Inflammatory-based indices; Overall survival; Prognostic nutritional index; Systemic treatment